A dynamical study of a rotor supported by a radial journal bearing incorporating a spherical squeeze film damper - Pham, Minh Hai; Nguyen, Xuan Ha; Nguyen, Minh Quan (JST: Engineering And Technology For Sustainable Development, 2021)
The reduction of noises, vibration and mechanical waves transmitting through water from the shells of submarines is essential to their safe operation and travelling. Vibrations from the rotors of the engines are widely deemed as one of the main sources to which engineers have tried to attenuate with various designs. Squeeze-film dampers can be easily integrated into rotor-bearing structures in order to lower the level of vibrations caused by rotors out of balance. For this advantage, squeeze-film dampers are widely used in air-turbine engines. This paper presents preliminary results of a numerical simulation of a shaft running on a journal bearing integrated with a squeeze-film damper and evaluates the capacity in reducing vibrations concerning the stability of static equilibrium of the shaft journal center. The proposed damper is designed in spherical shape with self-aligning capacity. The results were obtained using finite difference method and numerical integration of the full nonlinear equations of motion.